Cryptosporidium parvum Pyruvate Kinase Inhibitors With in vivo Anti-cryptosporidial Efficacy - Khan, Shahbaz M.; Zhang, Xuejin; Witola, William H. (Frontiers in Microbiology, 2022)
Cryptosporidium parvum is a highly prevalent protozoan parasite that causes a diarrheal disease in humans and animals worldwide. Thus far, the moderately effective nitazoxanide is the only drug approved by the United States Food and Drug Administration for treating cryptosporidiosis in immunocompetent humans. However, no effective drug exists for the severe disease seen in young children, immunocompromised individuals and neonatal livestock. C. parvum lacks the Krebs cycle and the oxidative phosphorylation steps, making it dependent solely on glycolysis for metabolic energy production. Within its glycolytic pathway, C. parvum possesses two unique enzymes, the bacterial-type lactate dehydrogenase (CpLDH) and the plant-like pyruvate kinase (CpPyK), that catalyze two sequential steps for generation of essential metabolic energy. We have previously reported that inhibitors of CpLDH are effective against C. parvum, both in vitro and in vivo. Herein, we developed an in vitro assay for the enzymatic activity of recombinant CpPyK protein and used it to screen a chemical compound library for inhibitors of CpPyK’s activity. The identified inhibitors were tested (at non-toxic concentrations) for efficacy against C. parvum using in vitro assays, and an in vivo mouse infection model. We identified six CpPyK inhibitors that blocked in vitro growth and proliferation of C. parvum at low micromolar concentrations (EC50 values ranging from 10.29 to 86.01 µM) that were nontoxic to host cells. Among those six compounds, two (NSC252172 and NSC234945) were found to be highly efficacious against cryptosporidiosis in immunocompromised mice at a dose of 10 mg/kg body weight, with very significant reduction in parasite load and amelioration of intestinal pathologies. Together, these findings have unveiled inhibitors for an essential molecular target in C. parvum and demonstrated their efficacy against the parasite in vitro and in vivo. These inhibitors are, therefore, potential lead-compounds for developing efficacious treatments for cryptosporidiosis.